A case of congenital central hypoventilation syndrome: A care report [Konjenital santral hipoventilasyon sendromu: Bir vaka takdimi] - (:unkn) unknown (My University, 2004)
Congenital central hypoventilation syndrome is a rare syndrome defined as the failure of automatic control of breathing, which, is present from birth, and of unknown etiology. In these patients, ventilation is more severely affected during sleep and they require chronic ventilation therapy. Although it is a rare disease, these patients can lead a long and good quality life as long as they are diagnosed timely and treated appropriately. In this paper, a 22-month-old patient is presented. She had required ventilatory support since birth and received home mechanical ventilation via tracheostomy at four months of age.
Keywords: Congenital central hypoventilation syndrome; Home mechanical ventilation